The Effects of Surface Roughness on the Durability of Polydopamine/PTFE Solid Lubricant Coatings on NiTiNOL 60. Issue 5 (3rd September 2019) - Miller, Charles; Choudhury, Dipankar; Zou, Min
Abstract: NiTiNOL 60, or 60NiTi, is a nickel–titanium alloy being investigated for bearing and gear applications. 60NiTi has many desirable properties for these applications; for example, it is hard, electrically conductive, highly corrosion resistant, superelastic, and nonmagnetic. However, its tribological performance is poor in unlubricated conditions. In this study, a polytetrafluorethylene (PTFE) coating with a polydopamine (PDA) adhesive underlayer was deposited on 60NiTi and evaluated for friction and wear reduction. Additionally, the effects of the substrate surface roughness on the tribological performance of the coating were investigated. The results showed that PDA/PTFE coating on 60NiTi reduced the coefficient of friction (COF) more than 85% and prevented wear of 60NiTi for thousands of rubbing cycles during accelerated tests. Furthermore, modifying the 60NiTi substrate surface through various grinding and polishing procedures increased the durability of the coating more than 30 times. Therefore, the coating and substrate surface combination showed the potential to provide solid lubrication for 60NiTi.